The Role of Inflammatory Mediators in the Failing Heart - Mann, Douglas L. (Springer US, 2001)
Although clinicians have recognized the importance of inflammatory mediators in the pathogenesis of heart disease for well over 200 years, it has taken nearly as many years for clinicians and scientists to focus on the basic biological mechanisms by which inflammatory mediators contribute to the pathogenesis of cardiac disease states. Over the past decade there has been increasing interest in the potential role that inflammatory mediators, play in a variety of cardiac disease states, including chronic heart failure. The Role of Inflammatory Mediators in the Failing Heart provides a state-of-the-art review on inflammatory mediators and the failing heart. This book will serve both as a useful introduction to the field, as well as an update for those interested in the role of inflammatory mediators and the failing heart
Keywords: Cardiology; Entzündung; Mediator; Herzinsuffizienz